2019
DOI: 10.1002/adsc.201900569
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 2‐Hydroxyalkyl Diarylphosphinates by Ruthenium‐Catalyzed Asymmetric Transfer Hydrogenation

Abstract: An asymmetric transfer hydrogenation of 2-oxo alkyl phosphinates in the presence of a chiral diamine ruthenium catalyst with HCOONa as a hydrogen source in aqueous 2,2,2-trifluoroethanol under mild conditions gave a wide range of chiral 2hydroxyalkyl diarylphosphinates in enantiomeric excesses of 97-99% and in good yields. The absolute configuration of the products was determined to be R by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
2
1
Order By: Relevance
“…These results highlight an oil–water interfacial effect that impacts the catalytic selectivity. It was previously found that “on water” effects and H-shuttle effects caused by the presence of water were reported to improve the reaction rate or alter the reaction selectivity. However, in our case, the selectivity enhancement should not be attributed to the effects arising from the presence of water molecules because the oil–water biphasic system gave much higher selectivity than the single water system (82.2% vs 71.5%). The presence of a liquid–liquid interface (biphasic system) should be responsible for the catalytic selectivity enhancement (Figure A­(c)).…”
Section: Resultscontrasting
confidence: 50%
“…These results highlight an oil–water interfacial effect that impacts the catalytic selectivity. It was previously found that “on water” effects and H-shuttle effects caused by the presence of water were reported to improve the reaction rate or alter the reaction selectivity. However, in our case, the selectivity enhancement should not be attributed to the effects arising from the presence of water molecules because the oil–water biphasic system gave much higher selectivity than the single water system (82.2% vs 71.5%). The presence of a liquid–liquid interface (biphasic system) should be responsible for the catalytic selectivity enhancement (Figure A­(c)).…”
Section: Resultscontrasting
confidence: 50%
“…The subsequent asymmetric transfer hydrogenation was carried out at 50 °C for 6 hours under nitrogen atmosphere. To our delight, the nucleophilic substitution and subsequent asymmetric transfer hydrogenation are compatible in a one‐pot process, giving chiral 1‐phenyl‐2‐(2,2,2‐trifluoroethoxy) ethanol ( 3 a ) in 56% yield and 94% ee (entry 1) [26g,h,27d,28] . Next, other chiral ruthenium complexes 4 b – 4 g , rhodium complex 4 h , and iridium complex 4 i were also screened (entries 2–9).…”
Section: Methodsmentioning
confidence: 99%
“…12 In 2019, Tang & Pan's group developed an electrochemical cross-dehydrogenation coupling to construct CN double bonds for the synthesis of rutaecarpine alkaloids (Scheme 2b). 13 To continue our interest in ether/O 2 promoted oxidative cleavage, 8 N -heterocyclic synthesis, 14 and green organic synthesis, 15 we report here an intramolecular oxidative dehydrogenative coupling for the construction of dihydroisoquinolino[2,1- a ]quinazolinones, 2-aryl quinazolinones, and analogues promoted by bis(2-methoxyethyl)ether in the presence of molecular oxygen under clean conditions (Scheme 2c).…”
Section: Introductionmentioning
confidence: 99%